Experimental College Fall '67 Hut D - Room 3 - San Francisco State College. Experimental College (San Francisco State College - Experimental College, 1967)
Brochure describing San Francisco State College Experimental College program and curriculum for the fall semester 1967, along with a history of the development of Experimental College